2017
DOI: 10.1590/01047760201723042447
|View full text |Cite
|
Sign up to set email alerts
|

ROOTSTOCK AGE AND GROWTH HABIT INFLUENCE TOP GRAFTING IN Araucaria angustifolia

Abstract: ABSTRACT:The objective of this study was to evaluate the technical viability and influence of the rootstock age and grafts growth habit on Araucaria angustifolia top grafting. Two rootstocks (8 and 35-year-old) were grafted with grafts originating from two growth habits (orthotropic and plagiotropic). We used the patch grafting technique in the middle and upper third of the crown of 8-year-old trees, and in the middle and lower third of 35-year-old trees, always near the apex in primary branches. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…Relatively low survival results, after six months of grafting, were obtained for both phenological stages (Table 7). However, some authors have indicated that the season influences the success of grafting [7][8][9]. In a study of grafts of Pinus patula Schiede ex Schltdl.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Relatively low survival results, after six months of grafting, were obtained for both phenological stages (Table 7). However, some authors have indicated that the season influences the success of grafting [7][8][9]. In a study of grafts of Pinus patula Schiede ex Schltdl.…”
Section: Discussionmentioning
confidence: 99%
“…For the grafting of Araucaria angustifolia (Bertol.) Kuntze in Parana, Brazil, in April (i.e., autumn, with scions in the dormant stage) with average temperatures that fluctuated between −3 • C and 18 • C and with a high relative humidity, a survival of 60% was reported at 12 months after grafting [7]. In our study, the survival decreased significantly after the second month of evaluation (March) onwards (Figure 4), which is attributed to the continual fluctuations in temperature (up to 42.59 • C) that were detected, and the low relative humidity that was registered within the greenhouse (38% on average).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations